The science planning process on the Rosetta mission. (April 2017) - Vallat, Claire; Altobelli, Nicolas; Geiger, Bernhard; Grieger, Bjoern; Kueppers, Michael; Muñoz Crego, Claudio; Moissl, Richard; Taylor, Matthew G.G.T.; Alexander, Claudia; Buratti, Bonnie; Choukroun, Mathieu; ,
Abstract: The Rosetta mission arrived at comet 67 P/Churyumov-Gerasimenko in Summer 2014, after more than 10 years in space. All previous mission encounters with a comet have provided a snapshot of the cometary activity at a given heliocentric distance. In contrast, Rosetta has escorted the comet nucleus for an extended period (>2 years) at a large range of cometo-centric and heliocentric distances, which has provided exceptional and unprecedented observing conditions to study, analyse and monitor 67 P during its passage to, through and away from perihelion. One of the biggest challenges of this mission is the development of an observation plan that adequately addresses the mission's science objectives while coping with a largely unknown and continuously evolving environment that constantly modifies the planning constraints. The Rosetta Science Ground Segment (RSGS), in support of the Project Scientist and the Science Working Team, is in charge of translating the high level mission science objectives into a low level pointing and operations plan. We present here the high-level science planning process adopted during the comet escort phase. We describe the main science objectives addressed along the mission lifetime, the different groups involved in the science planning, and the approach followed to translate those requirements into a viable and scientifically valid operations plan. Finally, we describe how the science planning scheme has evolved since arrival at the comet to react to the unexpected environment, largely reducing the planning lead times. Highlights: Detailed description of the science-driven operation planning of Rosetta. Translate mission science goals into an operation plan. Adapt the Rosetta science operation in a dynamical environment. Numerous challenges faced by science operation teams on a first-of-its-kind mission.